2022
DOI: 10.1177/07342829211056391
|View full text |Cite
|
Sign up to set email alerts
|

Single Versus Multiple Resilience Factors: An Investigation of the Dimensionality of the Academic Resilience Scale

Abstract: The Academic Resilience Scale (ARS) was developed to measure resilience factors in educational contexts. However, there is no clarity on whether the scale could be used as a measure of unidimensional academic resilience scores or just to obtain multidimensional academic resilience factors. How a scale is scored can affect the validity of inferences based on scores obtained by using the scale in research and practice. This study uses confirmatory factor analysis (CFA) and ancillary bifactor measures to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…Due to the significant difference between the scores in the post-test in the control and experimental groups, it was concluded that eliminating the pre-test factor (covariate) of computer educational games, reduces academic resilience. Comparison with previous results about the variable of academic resilience is consistent with the results of research ( Meneghel et al, 2019 ; Lepper and Malone, 2021 ; Singh, 2021 ; Hunsu et al, 2022 ; Ononye et al, 2022 ), and the study was not found to be inconsistent about the variable of academic resilience of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to the significant difference between the scores in the post-test in the control and experimental groups, it was concluded that eliminating the pre-test factor (covariate) of computer educational games, reduces academic resilience. Comparison with previous results about the variable of academic resilience is consistent with the results of research ( Meneghel et al, 2019 ; Lepper and Malone, 2021 ; Singh, 2021 ; Hunsu et al, 2022 ; Ononye et al, 2022 ), and the study was not found to be inconsistent about the variable of academic resilience of this study.…”
Section: Discussionsupporting
confidence: 91%
“…It is necessary to change the previous procedures to achieve such an approach. Old-fashioned teaching methods certainly do not meet the changing educational needs of the modern age; thus, the efforts of educational organizations should be related to information and communication technology and its application in the curriculum ( Singh, 2021 ; Hunsu et al, 2022 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Por el contrario, la vía conductual se caracteriza por identi#car las dimensiones de la resiliencia académica desde un enfoque adversidad-respuesta, que se ajusta mejor a la esencia de este constructo (Hunsu et al, 2022;Rudd et al, 2021). Esta perspectiva plantea que una medida realista de la resiliencia individual debe evaluar el modo de reaccionar del individuo y su capacidad de recuperación frente a eventos adversos/estresantes concretos (Hoge et al, 2007).…”
Section: Resiliencia Académica: Conceptualización Y Dimensionesunclassified
“…• Perseverancia: se re#ere a no rendirse y seguir intentando, englobando respuestas ligadas al sostenimiento del esfuerzo, mantener el interés y la convicción por las metas académicas planteadas, así como una reinterpretación optimista de la adversidad (Colp, 2015;Farrington et al, 2012;Morton et al, 2014). • Reflexión y búsqueda adaptativa de ayuda: este factor abarca respuestas adaptativas orientadas a ejercer control sobre la situación problemática mediante la re"exión sobre las propias fortalezas y debilidades, la activación de mecanismos de autorregulación del aprendizaje, tener iniciativa para pedir ayuda y mostrar recursividad mediante el aprovechamiento de recursos personales y sociales (Ayala & Manzano, 2018;De la Fuente et al, 2017;He, 2014;Hunsu et al, 2022). • Afecto negativo y respuesta emocional: este factor corresponde a la autoprotección afectiva mediante la gestión adecuada de las emociones negativas, mostrando capacidad para regular y mantener en niveles bajos a respuestas emocionales como la ansiedad, la decepción, el catastro#smo o la frustración (Colp, 2015;Hunsu et al, 2022;Martin & Marsh, 2006).…”
Section: Resiliencia Académica: Conceptualización Y Dimensionesunclassified
“…A foundational assumption in the polytomous IRT models is unidimensionality. In practice, many constructs and corresponding measures are multidimensional, such as the Resilience Scale and Cushing Syndrome Scale (Depaoli et al, 2018;Hunsu et al, 2022). As a result, the unidimensionality assumption of IRT models is violated, and consequently, multidimensional IRT models such as the multidimensional GRM (MGRM) are proposed to ensure a deeper grasp of how multiple constructs in the instrument are measured by the item sets.…”
Section: Introductionmentioning
confidence: 99%